2009
DOI: 10.1243/09544070jauto1040
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on the mixing characteristics of exhaust gas recirculation gases with air, and their dependence on system geometries in four-cylinder engine applications

Abstract: To achieve low nitrogen oxide (NO x ) emissions and combustion reliability, the variation in the geometry of the exhaust gas recirculation (EGR) system should be optimized. However, the layout process essentially fixes the position of a conventional EGR system, and modifying the intake manifold geometry tends to be economically unjustifiable for a commercial engine. In the present study, two types of EGR system, namely 'linked single' and 'individual' EGR systems, are proposed and their performances are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They showed that the hydrogen enrichment has a good impact on the incylinder flow characteristics and engine performance. Kim et al (2009) studied numerically the performance of two-different Exhaust Gas Recirculation (EGR) systems in order to reduce the pollutants emissions and improve the combustion behavior. They performed a three-dimensional combustion calculation using the commercial code STAR-CD and the standard k-ε turbulence model.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the hydrogen enrichment has a good impact on the incylinder flow characteristics and engine performance. Kim et al (2009) studied numerically the performance of two-different Exhaust Gas Recirculation (EGR) systems in order to reduce the pollutants emissions and improve the combustion behavior. They performed a three-dimensional combustion calculation using the commercial code STAR-CD and the standard k-ε turbulence model.…”
Section: Introductionmentioning
confidence: 99%